Kajian Rencana Pengembangan Desain Kebun Raya Tinjomoyo Kota Semarang - Rahayuningsih, Margareta; Sidiq, Wahid Akhsin Budi Nur; Wicaksono, Dimas; Widodo, Agus Ananto; Setyowati, Nanik (Badan Riset dan Inovasi Daerah Kota Semarang, 2024)
Semarang City has a fairly complete biodiversity ranging from genetic, species, and ecosystem levels. In addition, some of the plants identified are related to the historical value and local wisdom of Semarang City. However, the existence of some of these plants is currently threatened by the massive development of Semarang City and the reduction of green spaces. One of the solutions to conserve plants and maintain green spaces in Semarang City is through the development of Tinjomoyo Botanical Garden. The purpose of the study is to develop a design for the development of Tinjomoyo Botanical Garden in accordance with the ecoregion of Semarang City which is included in the East Java Rainforest with the concept of techno park. The design of the Tinjomoyo Botanical Garden is done through zoning arrangements that refer to the Semarang City Ecoregion which is included in the East Java Rainforest. The study results show zone IV with an area of about 10.04 hectares which is the zone with the highest level of suitability for the development of Tinjomoyo Botanical Garden. The arrangement of the botanical garden area, including the reception zone, management zone, collection zone, and recreation zone. In the collection zone 135 plant species as the initial collection of Tinjomoyo Botanical Garden, with a total of 1,834 individuals or collections divided into 8 categories, including historical plants, fruit plants, rare plants, endemic plants, aromatic plants, medicinal plants, forest zones and ornamental plants. Tinjomoyo Botanical Garden is planned to be built within the next 5 years in stages according to the urgency of development in each zone. Suggestions given in the development of Tinjomoyo Botanical Garden needs involvement, coordination, and cooperation with various sectors in order to develop and continue.